Design and Development of Solar Powered Water Purifier - Dr. Sunil Kumar K; Arun Kumar B R; K C Saqhib Pasha; Naveenkumar Y M; Nithish K (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
A solar-powered water purifier is an innovative solution that utilizes solar energy to provide clean drinking water. This system harnesses the sun’s power to drive purification processes such as filtration, distillation, or ultraviolet (UV) sterilization, eliminating contaminants like bacteria, viruses, and chemicals. It is energy-efficient, eco-friendly, and ideal for remote or off-grid areas where access to electricity is limited. By combining renewable energy with water purification technology, solar-powered purifiers offer a sustainable way to improve water quality while reducing reliance on traditional power sources.